Molecular Mechanisms Involved in Biosynthesis and Regulation of Carotenoids in Plants - P Shilpa (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2016)
Carotenoids are coloured compounds beneficial to plants and humans. Some of the major health benefits carotenoids provide include Vitamin A precursors and, antioxidants besides being involved in several physiological functions. Even though several carotenoids are synthesised by plants, only a few like beta/ alpha carotenes and cryptoxanthin serve as Vitamin A precursors. The rest are useful as antioxidants. To draw maximum benefits from carotenoids, we need to incorporate these in crop improvement programmes for enhancing available Vitamin A precursor carotenoids. Therefore, it is essential to study biosynthesis of carotenoids, their genetics and their control. In this review, we focus on factors regulating carotenoid biosynthesis, metabolism and storage in plastids. Transcriptional and genetic control of carotenoid production in plants is discussed in the review using several mutants too. Further, environmental regulation of carotenoid biosynthesis is also highlighted. Carotenoid-rich fruits and vegetables have greater economic value owing to their health-promoting effects. Besides,carotenoids have several industrial applications. Therefore, knowledge of regulation mechanism in carotenoid production in plants can help develop crop varieties or technologies, thus generating carotene-rich fruits and vegetables.